Inhibitory Effects of Chaga (Inonotus Obliquus) on Tumor Promotion in Two-Stage Mouse Skin Carcinogenesis - Ayako Akita; Yi Sun; Ken Yasukawa (Journal of Pharmacy and Nutrition Sciences, 2015)
The methanol extract of chaga (sclerotia of Inonotus obliquus) inhibited the promoting effect of 12-O-tetradecanoylphorbol-13-acatate (TPA) applied twice weekly on skin tumor formation in mice initiated with 7,12-dimethylbenz [a] anthracene. The methanol extract from chaga led to the isolation of eight triterpenoids (1-8). The anti-inflammatory activity of the isolated lanostane-type triterpenes was evaluated against TPA-induced inflammatory ear edema in mice. These compounds showed markedly anti-inflammatory effects, with a 50% inhibitory dose of 125-458 nmol/ear.